Application of Innovative Learning Media Utilizing the Internet in History Education Merdeka Curriculum (MBKM) Campus Teaching Program at SMKN7 Palu - Hasan; Moh Rifaldi (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study explores the impact of the internet on learning at SMK Negeri 7 Palu, focusing on studentslearning outcomes. Data was collected through Merdeka Curriculum (MBKM) Campus Teaching Programactivities, interviews, and documentation. The research demonstrates that the internet enhances studenlearning results in history subjects at SMK Negeri 7 Palu. Internet media can influence students' classroomlearning activities by elucidating specific learning objectives and facilitating accurate assessment. Thinternet offers diverse educational resources and a dynamic learning experience through visuals andaudio, enhancing student engagement in history education. The impact of internet media on enhancinstudent learning outcomes has significantly contributed to their academic success. The study highlightsthe importance of the internet in enhancing the learning process and promoting a more inclusive andeffective learning environment.